2002
DOI: 10.1152/jn.00575.2001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glutamatergic Synaptic Input to Spinal Lamina IIoNeurons by Presynaptic α2-Adrenergic Receptors

Abstract: Activation of spinal alpha(2)-adrenergic receptors by the descending noradrenergic system and alpha(2)-adrenergic agonists produces analgesia. However, the sites and mechanisms of the analgesic action of spinally administered alpha(2)-adrenergic receptor agonists such as clonidine are not fully known. The dorsal horn neurons in the outer zone of lamina II (lamina II(o)) are important for processing nociceptive information from C-fiber primary afferents. In the present study, we tested a hypothesis that activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 45 publications
5
97
0
Order By: Relevance
“…Clonidine also significantly reduces capsaicin-evoked glutamate release from the primary afferent nerves (Ueda et al, 1995). This evidence supports the notion that presynaptic α 2 -adrenergic receptors play an important role in the regulation of the glutamatergic synaptic input to spinal dorsal horn neurons, which could contribute to the analgesic actions produced by α 2 -adrenergic receptor agonists (Pan et al, 2002b). Interestingly, removal of α 2A -adrenergic receptors on TRPV1-expressing afferent neurons paradoxically potentiates the antinociceptive effect produced by intrathecal injection of clonidine in rats (Chen et al, 2007a).…”
Section: Effect Of α 2 -Adrenergic Receptor Agonists On Synaptic Transupporting
confidence: 80%
See 1 more Smart Citation
“…Clonidine also significantly reduces capsaicin-evoked glutamate release from the primary afferent nerves (Ueda et al, 1995). This evidence supports the notion that presynaptic α 2 -adrenergic receptors play an important role in the regulation of the glutamatergic synaptic input to spinal dorsal horn neurons, which could contribute to the analgesic actions produced by α 2 -adrenergic receptor agonists (Pan et al, 2002b). Interestingly, removal of α 2A -adrenergic receptors on TRPV1-expressing afferent neurons paradoxically potentiates the antinociceptive effect produced by intrathecal injection of clonidine in rats (Chen et al, 2007a).…”
Section: Effect Of α 2 -Adrenergic Receptor Agonists On Synaptic Transupporting
confidence: 80%
“…Electrophysiological studies using rat spinal cord slices have demonstrated that clonidine can inhibit synaptic glutamate release from primary afferent nerves to spinal dorsal horn neurons (Pan et al, 2002b). Clonidine also significantly reduces capsaicin-evoked glutamate release from the primary afferent nerves (Ueda et al, 1995).…”
Section: Effect Of α 2 -Adrenergic Receptor Agonists On Synaptic Tranmentioning
confidence: 99%
“…The spinal cord transverse slices (300 m in thickness) with an attached dorsal root were prepared as described previously Pan et al 2002). Briefly, the lumbosacral segment of the spinal cord of Sprague-Dawley rats (5-6 wk old, Harlan, Indianapolis, IN) was rapidly removed using halothane anesthesia and cut in a preoxygenated ice-cold sucrose artificial cerebrospinal fluid (ACSF) using a vibratome (Technical Product International, St. Louis, MO).…”
Section: Spinal Cord Slice Preparationmentioning
confidence: 99%
“…Lamina II is an important region for modulation of nociceptive information and regulation of the firing activity of dorsal horn projection neurons (Cervero and Iggo 1980;Li et al 2002;Lu and Perl 2003;Yoshimura and Jessell 1989;Yoshimura and Nishi 1995). Recent neuroanatomical studies have shown that the isolectin-B4-positive C-fiber afferents predominantly terminate at lamina II o (Pan et al 2003;Woodbury et al 2000). Furthermore, nociceptive neurons are mostly found in lamina I and II o and innocuous mechanoreceptive cells are mostly located in lamina II i (Light and Willcockson 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, discrepancies are noted between the α 2 subtypes as defined by message and immunohistochemistry (see [91]). Spinal α 2 adrenergic receptors display several characteristics: i) binding is present presynaptically on C-fibers and postsynaptically on spinal neurons; ii) agonists are believed to alter spinal nociceptive processing by preventing opening of voltage-sensitive Ca channels (blocking release) [92,93] and increasing potassium conductance leading to hyperpolarization of dorsal horn neurons through increased pK conductance [87,88,94,95]. Consistent with their pharmacology, the analgesic activity is reversed by α 2 antagonists such as atipamezole [96][97][98].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%